Fast Determination of Short-Chain Fatty Acids and Glucose Simultaneously by Ultraviolet/Visible and Refraction Index Detectors via High-Performance Liquid Chromatography - Serafim, Jéssica Aparecida [UNESP]; Silveira, Raiza Felismino [UNESP]; Vicente, Eduardo Festozo [UNESP] (Springer Nature, 2021)
A rapid analytical method for simultaneous quantification of glucose (GLC) and seven short-chain fatty acids (SCFA) was developed for detection of ruminal fermentation parameters. The formic acid (FA), lactic acid (LA), acetic acid (AA), propionic acid (PA), butyric acid (BA), isovaleric acid (IVA), valeric acid (VA), and glucose were identified and quantified by high-performance liquid chromatography (HPLC) technique, using a reverse-phase column (C-18) and simultaneous detection in UV-Vis and Refraction Index (RID) detectors, linked in series. The method was validated following the requirements of selectivity, linearity, sensitivity, limit of detection, limit of quantification, accuracy, and precision. The developed method operates in isocratic and gradient modes, providing a better SCFA separation, which allows their determination with a high accuracy and repeatability. Therefore, this study provides a fast, reliable, accurate, straightforward, and efficient alternative method for analysis of ruminal fermentation parameters by liquid chromatography using both detectors simultaneously.
Keywords: Analysis; HPLC; RID; Ruminal fermentation; SCFA; UV-Vis